2004
DOI: 10.1002/hon.728
|View full text |Cite
|
Sign up to set email alerts
|

An efficient therapeutic approach to patients with acute promyelocytic leukemia using a combination of arsenic trioxide with low‐dose all‐trans retinoic acid

Abstract: The use of arsenic trioxide (As2O3, ATO) combined with all-trans retinoic acid (ATRA) has recently been reported to induce remission in patients with acute promyelocytic leukemia (APL). However, its efficiency remains inconclusive mainly due to the small number of the available cases. In this study, therefore, we present a clinical study using a combination of ATO with low-dose ATRA (LD-ATRA) to treat 108 APL patients (80 newly diagnosed patients, 28 relapsed patients). Therapeutic outcomes using the ATO/LD-AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 17 publications
2
40
0
Order By: Relevance
“…The detailed information with regard to the dose, time course, interval, and overall regimen design of ATRA, ATO, and chemotherapy during remission induction, consolidation and maintenance therapy has been described previously (16). The benefits of combining ATRA with ATO for newly diagnosed APL, which were statistically significant over a median follow-up of 18 months in our trial, were published in 2004 (16) and got support from some recent reports (18,19), and patients who thereafter entered the trial requested this treatment regimen. As a result of a meticulous evaluation of our trial in terms of both clinical outcome and ethics, we terminated the randomized grouping and prescribed the ATRA/ATO-based regimen for induction and postremission therapy for the maximal benefit of patients.…”
Section: Accrual Of Patientssupporting
confidence: 56%
See 1 more Smart Citation
“…The detailed information with regard to the dose, time course, interval, and overall regimen design of ATRA, ATO, and chemotherapy during remission induction, consolidation and maintenance therapy has been described previously (16). The benefits of combining ATRA with ATO for newly diagnosed APL, which were statistically significant over a median follow-up of 18 months in our trial, were published in 2004 (16) and got support from some recent reports (18,19), and patients who thereafter entered the trial requested this treatment regimen. As a result of a meticulous evaluation of our trial in terms of both clinical outcome and ethics, we terminated the randomized grouping and prescribed the ATRA/ATO-based regimen for induction and postremission therapy for the maximal benefit of patients.…”
Section: Accrual Of Patientssupporting
confidence: 56%
“…We showed that the ATRA/ATO combination significantly shortened the time to achieve CR, reduced disease burden, and enhanced DFS compared with approaches based on the use of either ATRA or ATO as single agents (16). These benefits of the ATRA/ATO-based combination were subsequently confirmed by several groups (17)(18)(19). Being aware of these advances, APL patients entering into our clinical trials preferred ATRA/ATObased treatment to gain maximal therapeutic efficacy.…”
mentioning
confidence: 77%
“…As a follow-up to mice studies, several clinical trials were done to see if this therapeutic synergy could be translated into treatment strategies for APL patients. These studies have all shown a striking similarity in APL patients with regard to disease eradication by RA-As (7,(81)(82)(83). Patients treated with a combination of RA and arsenic obtained a quicker clinical response, had a more rapid and complete clearance of leukemic cells, and had a significantly longer period of relapse-free survival.…”
Section: Clinical-translational Advancesmentioning
confidence: 91%
“…These trials are conducted mainly on the basis of successful studies in animal models, showing a positive effect of ATRA/ATO combinations in APL mice (Jing et al, 2001;Lallemand-Breitenbach et al, 1999). The main conclusion so far from the ongoing clinical studies is that newly diagnosed patients are likely to benefit from ATRA/ATO combination treatment in addition to low-dose chemotherapy (Estey et al, 2006;Hu et al, 2009;Shen et al, 2004;Wang et al, 2004).…”
Section: Present and Future Apl Therapymentioning
confidence: 99%
“…While ATRA and ATO on their own are known to be effective in curing APL, it is also becoming increasingly clear that treatment regiments based on a combination of the two drugs leads to a quicker clinical remission, a more effective clearance of leukemic cells and a significantly longer period of relapse free survival (Estey et al, 2006;Hu et al, 2009;Shen et al, 2004;Wang et al, 2004). This synergistic effect may result due to the ability of both these drugs to cause PML/RARA degradation, a parameter that appears to be critical for the success of APL therapy.…”
Section: The Synergy Between Atra and Atomentioning
confidence: 99%